Similarity Networks for the Construction of Multiple-Fault Belief Networks - Heckerman, David (1990)
A similarity network is a tool for constructing belief networks for the diagnosis of a single fault. In this paper, we examine modifications to the similarity-network representation that facilitate the construction of belief networks for the diagnosis of multiple coexisting faults.
Stanford University Interactive Workspaces Project Technical Note 2001-1